Recombinant human islet amyloid polypeptide forms shorter fibrils and mediates β-cell apoptosis via generation of oxidative stress - Dubey, Richa; Minj, Pooja; Malik, Nikita; Sardesai, Devika M; Kulkarni, Shruti H; Acharya, Jhankar D; Bhavesh, Neel Sarovar; Sharma, Shilpy; Kumar, Ashutosh (Biochemical journal, 2017)
Protein misfolding and aggregation play an important role in many human diseases including Alzheimer's, Parkinson's and type 2 diabetes mellitus (T2DM). The human islet amyloid polypeptide (hIAPP) forms amyloid plaques in the pancreas of T2DM subjects (>95%) that are involved in deteriorating islet function and in mediating β cell apoptosis. However, the detailed mechanism of action, structure and nature of toxic hIAPP species responsible for this effect remains elusive to date mainly due to the high cost associated with the chemical synthesis of pure peptide required for these studies. In the present work, we attempted to obtain structural and mechanistic insights into the hIAPP aggregation process using recombinant hIAPP (rhIAPP) isolated from Results from biophysical and structural studies indicate that the rhIAPP self-assembled into highly pure, β-sheet-rich amyloid fibrils with uniform morphology. rhIAPP-mediated apoptosis in cells was associated with increased oxidative stress and changes in mitochondrial membrane potential. The transcript levels of apoptotic genes - and were found to be up-regulated, while the levels of the anti-apoptotic gene - were down-regulated in rhIAPP-treated cells. Additionally, the expression levels of genes involved in combating oxidative stress namely , and were down-regulated. rhIAPP exposure also affected glucose-stimulated insulin secretion from isolated pancreatic islets. The aggregation of rhIAPP also occurred significantly faster when compared with that of the chemically synthesized peptide. We also show that the rhIAPP fibrils were shorter and more cytotoxic. In summary, our study is one among the few to provide comprehensive evaluation of structural, biophysical and cytotoxic properties of rhIAPP.